Mixing Ice: DJ Spooky’s Musical Portraits of the Arctic and Antarctic - Carolyn Philpott (2020)
In recent decades, increasing numbers of professional composers, musicians and sound artists from diverse national and cultural backgrounds have turned their attention towards the polar regions to gain inspiration for new creative works. This trend can be attributed to several factors, including the celebration of centenaries of Heroic-Era expeditions, the rise in media reporting about environmental changes in the polar regions and the implications for global climate processes, the increased dialogue about these places within literature and the arts, and the greater opportunities for artists to physically visit them through tourist cruises/flights and arts residency programs. While some composers, musicians and sound artists have focused their attention on one of the polar icescapes, rather than both, collectively their work reflects on the uniqueness and importance of the polar regions, the history of human presence within them, and the influences of these places on the spaces in between.